Comparative effectiveness of Tuina therapy versus manual physical therapy for knee osteoarthritis: a randomized controlled trial - Peihong Ma; Luping Liu; Sina Li; Meiling Cai; Siyu Han; Zhiwen Weng; Qianji Chen; Yixuan Gao; Lingyun Zhang; Guiyun Wu; Xiaoming Yang; Yang Zhang; et al. (BMC Complementary Medicine and Therapies)
Abstract Background Tuina therapy (Tuina) is commonly utilized for managing knee osteoarthritis (KOA), yet the available evidence is limited. This study aimed to evaluate the effectiveness of Tuina compared to widely accepted manual physical therapy (mPT) for patients with KOA. Methods Between Oct 2019 and Oct 2021, patients with KOA (Kellgren-Lawrence score II or III) were randomly assigned in a 1:1 ratio to receive Tuina or mPT, with eight 20-min sessions over 3 weeks. Assessments were performed at baseline, week 4, 8, and 16. The primary outcome was the change of total Western Ontario and McMaster University Osteoarthritis Index (WOMAC) from baseline to week 4. Secondary outcomes included WOMAC subscales, knee pain measures, performance-based tests, quality-of-life measures, and safety assessments. Patients, evaluators, and statisticians were blinded to treatment group assignment. All main analyses were by intention-to-treat. Results Of the 140 patients allocated to Tuina or mPT, 127 completed the treatment. There was significant intervention × time interaction observed in the WOMAC-total (F(2, 266) = 3.87, P = 0.02), there was no statistically significant between groups at week 4 (between-group difference: −1.00, 95%CI: −5.33 to 3.33, P = 0.79, Bonferroni correction). By week 8, Tuina showed significantly consistent improvement compared to mPT (between-group difference: −4.33, 95%CI: −8.34 to −0.31, P = 0.03, Bonferroni correction), whereas there were no statistically significant differences between groups at week 16 (between-group difference: 0.74, 95%CI: −3.67 to 5.15, P = 0.37, Bonferroni correction). Most secondary outcomes showed no significant between-group differences, except for the Timed Up and Go Test Time favoring mPT (0.94, 95%CI: 0.03 to 1.85, P = 0.04). No serious adverse events occurred. One patient in the mPT group took the medication and no patients received other therapies for KOA. Conclusions Tuina produced beneficial effectiveness similar to mPT in treating KOA. Trial registration NCT03966248, Registered on 29/05/2019, ClinicalTrials.gov.